2016
DOI: 10.9734/bjmmr/2016/26308
|View full text |Cite
|
Sign up to set email alerts
|

Material Selection for Constructing an Intraoral Stent Used in Radiotherapy: Analysis of Density and Structure

Abstract: Neck and head cancer is a very common disease. Radiotherapy is one of the treatments, and its side effects affect the patient's quality of life because the radiation targets both neoplastic and healthy tissues. This study aimed to select material that exhibited the greatest number of Original Research Articlecharacteristics that are biocompatible with human tissue and that are strong enough to construct an intraoral stent. The stent would be used to mechanically isolate the palate, tongue, and mouth floor to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Typically, only two consultations are required: one to determine the size of the mandible and maxilla and the other to build the anterior abutments [ 7 , 9 ]. Acrylic resin is considered the ideal material for manufacturing this device because it is a non-toxic, durable, and low-cost substance that does not interact with radiation [ 7 , 30 ]. Hence, acrylic resin was the dental material selected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, only two consultations are required: one to determine the size of the mandible and maxilla and the other to build the anterior abutments [ 7 , 9 ]. Acrylic resin is considered the ideal material for manufacturing this device because it is a non-toxic, durable, and low-cost substance that does not interact with radiation [ 7 , 30 ]. Hence, acrylic resin was the dental material selected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Four materials were selected: Polyacetal (white and black), polymethylmethacrylate (PMMA) polyurethane, and polyvinyl chloride (PVC). The study concluded that PMMA showed the ideal density for making these protective stents [30] .…”
Section: Main Textmentioning
confidence: 98%
“…The elementary material of the intraoral stents should not irritate the oral mucosa. It should be non-toxic, inert, thermo-mechanically resistant, and easy to handle [30] .…”
Section: Main Textmentioning
confidence: 99%
“…Most of intraoral prosthesis for radiotherapy are made of polymethylmethacrylate (PMMA), an acrylic resin used for laboratory techniques for dental prosthesis, presenting an atomic number close to that of the water, with excellent structural resistance [11][12][13][14][15]. Some authors have already described the use of thermoplastics to produce such devices, as ethylene vinyl acetate [16,17], polyester [18] and polyethylene terephthalate (PET) [19,20].…”
Section: Introductionmentioning
confidence: 99%